Upaya Meningkatkan Hasil Belajar Siswa Materi Bangun Datar Dengan Berbantu Media Papan Kepastian Pada Kelas IV Sekolah Dasar - Teguh Yunianto (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2023)
This research was conducted with the aim of improving learning outcomes through certainty board learning media in mathematics subject matter of flat shapes. This type of research was classroom action research using a class action research flow design. This research was conducted during the second cycle. Each cycle consists of four stages, namely action planning, action implementation, observation and reflection. The subjects of this study were class V SD Negeri 5 Bandar Agung East Lampung Regency as many as 9 students, of whom were 6 boys and 3 girls. The research source was obtained from observations of teacher and student activities in the form of written tests of student learning outcomes. The results of the study showed that there was an increase. Pre cycle of 22.22%, Cycle one of 55.55%, and cycle two of 88.88%. From the results of the implementation and research on learning outcomes, it can be determined that the implementation of using certainty board learning media can improve student learning outcomes in flat bagum material in class IV SD Negeri 5 Bandar Agung